2015
DOI: 10.1039/c5mb00432b
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity effects of atrazine-induced SH-SY5Y human dopaminergic neuroblastoma cells via microglial activation

Abstract: Atrazine (2-chloro-4-ethytlamino-6-isopropylamine-1,3,5-triazine; ATR) is a broad-spectrum herbicide with a wide range of applications worldwide. However, ATR is neurotoxic; it reduces dopamine levels in the substantia nigra and corpus striatum in the midbrain, affects the absorption of synaptic vesicles and synaptic bodies, and interferes with dopamine storage and uptake in synaptic vesicles, leading to neurodegenerative disorders. Microglia are resident immunocompetent and phagocytic cells that regulate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 76 publications
(177 reference statements)
0
22
0
1
Order By: Relevance
“…In previous reports, we demonstrated that ATR reduces cell viability in a time- and dose-dependent manner and found that the median lethal dose (LD 50 ) of ATR was 250 µM after a 24 h exposure [27]. Therefore, we used ATR at 250 µM for further experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous reports, we demonstrated that ATR reduces cell viability in a time- and dose-dependent manner and found that the median lethal dose (LD 50 ) of ATR was 250 µM after a 24 h exposure [27]. Therefore, we used ATR at 250 µM for further experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, ATR can significantly change the levels of catecholamine neurotransmitters, especially norepinephrine (NE) and DA. In addition to the effects of ATR on DA in the nervous system, studies have shown that ATR induces apoptosis and reactive oxygen species (ROS) levels in SH-SY5Y cells [26, 27]. Other results show that ATR induces apoptosis in PC12 cells by altering the expression of p53, caspase-3 and caspase-9 [28].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was found that there is a possible statistical relationship between triazine herbicides and breast cancer incidence ( 104 ). Atrazine is the most known of the triazines, and it is a very widely used herbicide that has been associated with oxidative stress ( 103 ), cytotoxicity ( 105 , 106 ), and dopaminergic effects ( 107 , 108 ). Furthermore, the exposure of experimental animals to atrazine has been associated with reproductive toxicity ( 109 ) and delays in sexual maturation ( 110 ).…”
Section: Other Classes Of Chemical Pesticidesmentioning
confidence: 99%
“…Histidine decarboxylase is the only enzyme that converts histidine to histamine, which is an important bioamine that contributes to inflammation, allergies, and neurotransmission (Ku et al, 2014). Although not investigated as predominately as the neuroendocrine dysfunction caused by atrazine, the inflammatory and immune responses are currently under investigation (Ma et al, 2015; Thompson et al, 2015; Zhao et al, 2013). As hdc expression is predominantly altered in adult male brain tissue, these data could provide support for further studies investigating the immune responses later-in-life following an embryonic atrazine exposure.…”
Section: Discussionmentioning
confidence: 99%